Keadilan Sosial tentang Iddah bagi Laki Laki Perspektif Mahmud Muhammad Thaha - Baihaqi, Muhammad Ibnu Hibban (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
The provisions of  iddah  are closely associated with women, while there are no explicit explanations in the Qur'an or Syafi’iyyah texts regarding  iddah  for men. This article explores  iddah  for men using the framework of Mahmud Muhammad Thaha’s thought.  Iddah  for women is considered discriminatory by the millennial generation. This study employs a normative juridical approach, which is based on legal materials focusing on primary and secondary sources. The rise of feminist movements has spurred significant resistance and demands to challenge practices perceived as discriminatory toward women. Mahmud Muhammad Thaha, a thinker known for his innovative ideas in Islam, divides Islam into two periods: the Meccan and Medinan periods. The Meccan period is characterized by a strong emphasis on human rights, egalitarianism, and social justice. In contrast, the Medinan period primarily focuses on Islamic law with a structured and sharia-oriented approach. The idea of  iddah  for men, viewed through the lens of Mahmud Muhammad Thaha’s egalitarian and justice-centered approach, offers a viable framework for discussion. These findings can support the reform of Islamic law, particularly in matters related to social justice, such as the  iddah  period for men. The Meccan values provide a foundation for formulating more inclusive and responsive legal frameworks that align with the needs of modern society. Furthermore, the government circular highlighted in this research serves as a model for introducing gender-equitable Islamic legal policies by emphasizing the psychological and social aspects of sharia regulations.